Improving the voltage profiles of Distribution Networks using multiple Distribution Generation Sources - AlHajri, M.F.; El-Hawary, M.E. (2007 Large Engineering Systems Conference on Electric Power Engineering, 2007)
Installing Distribution Generation (DG) in the distribution level has positive impacts on the system voltage profile as well on the substations' capacity. However the extent of such benefits depends greatly of the DG size and location. Heavily loaded systems need more than one DG to rectify the voltage profile and to achieve other DG promised benefits. In this paper the number of Distribution Generators (DGs) and their sizes are investigated thoroughly for installing single and multiple DGs. The optimal DG number and sizing are formulated as NonLinear Programming (NLP) problem subject to boundary restriction and nonlinear equality and inequality constraints imposed on the system. In this paper, a radial distribution case study comprises of 33-Bus is tested. A comparative study is performed to evaluate three DG situations. The original system with no DG added is evaluated first, then single and multiple DG installations are assessed later in this research.